Conserved and Unique Roles of Chaperone-Dependent E3 Ubiquitin Ligase CHIP in Plants - Zhang, Yan; Xia, Gengshou; Zhu, Qianggen (Frontiers in Plant Science, 2021)
Protein quality control (PQC) is essential for maintaining cellular homeostasis by reducing protein misfolding and aggregation. Major PQC mechanisms include protein refolding assisted by molecular chaperones and degradation of misfolded and aggregated proteins by the proteasome and autophagy. C-terminus of heat shock protein 70 (Hsp)70-interacting protein (CHIP) is a chaperone-dependent and U-box-containing E3 ligase. CHIP is a key molecule in PQC by recognizing misfolded proteins through its interacting chaperones and targeting their degradation. CHIP also ubiquitinates native proteins and plays a regulatory role in other cellular processes including signaling, development, DNA repair, immunity and aging in metazoans. As a highly conserved ubiquitin ligase, plant CHIP plays a critical role in responses to a broad spectrum of biotic and abiotic stresses. CHIP protects chloroplasts by coordinating chloroplast PQC both outside and inside the important photosynthetic organelle of plant cells. CHIP also modulates the activity of protein phosphatase 2A, a crucial component in plant signaling network including abscisic acid signaling. In this review, we discuss the structure, cofactors, activities and biological function of CHIP with an emphasis on both its conserved and unique roles in PQC, stress responses and signaling in plants.